Analysis of Profitability and Profit Margins of Rice-Fish Farming (Integrated Rice-Fish System) in Karangbinangun District, Lamongan Regency, East Java - Ika Purnamasari; Nurkholifah Dwi Rahayu; M. Khairul Anam; Dona Wahyuning Laily (Universitas Islam Lamongan, 2024)
In its development, rice and fish cultivators (pond rice fields) in Karangbinangun District find it difficult to determine whether the production yields they will receive result a profit or a loss. Because remember that there are many problems by cultivators such as the difficulty of getting fertilizer, the high cost of fertilizer, fish seeds are not always available, labor is hard to find, while the majority of cultivators in Karangbinangun District are small scale, so the capital they have is also small. Therefore, there is a need for research on 1) analysis of the costs incurred by pond rice fields cultivators for one year, 2) profit analysis, and 3) Profitability analysis. The analytical method used in this research is business financial analysis which consists of cost analysis, profit analysis and profitability analysis. The result of the research is average total costs incurred by rice-fish cultivation businesses (pond rice fields) are IDR 69,041,732.03/Ha/Year and the revenue is IDR 153,560,000/Ha/Year so that the profit received is IDR 84,518,267.97/Ha/Year. The R/C Ratio value is 2.22 and the net profit ratio (Net Profit Margin) is 55.04%, which means that the rice-fish cultivation business (pond rice fields) is efficient and the farmer's decision to undertake rice-fish cultivation (pond rice fields) it's still very much worth continuing